The Physical and Cognitive Performance Test for Residents in Assisted Living Facilities. Issue 7 (8th May 2017) - Bowen, Mary Elizabeth; Rowe, Meredeth; Ersek, Mary; Ibrahim, Said; Shea, Judy A.
Abstract : Objectives: To develop and evaluate the psychometric properties of a new performance‐based instrument (Physical and Cognitive Performance Test for Assisted Living Facilities (PCPT ALF)) designed to assess the physical and cognitive skills associated with performance of activities of daily living (ADLs) and instrumental activities of daily living (IADLs). Design: There were three stages in this study: development of instrument items and validity testing, a feasibility pilot study, and a cross‐sectional trial to establish construct and criterion validity and reliability. Setting: One 116‐bed assisted living facility (ALF). Participants: After a pilot test with 10 residents, a cross‐sectional trial was conducted with 55 additional residents. Measurements: The Barthel Index and Functional Independence Measure were used to estimate criterion validity. Construct validity was examined using exploratory factor analyses (EFAs). Results: Disattenuated correlations between the PCPT ALF and other tools were all greater than 0.72, supporting criterion validity. Internal consistency (physical ability, α = 0.95; cognitive support, α = 0.92) and 1‐week test–retest reliability (PCPT ALF, P = .93) were high, as was interrater reliability (IRR) (physical ability, 0.99; cognitive support, 1.00). In two EFAs, a one‐factor solution accounted for 64.1% of the variance for the physical ability subscale and 63.5% of the variance for the cognitive support subscale. Conclusion: The findings provide early evidence of the PCPT ALF's validity and reliability. If confirmed, this study's findings may be used in future work to assess the success of interventions to prevent or slow decline in the skills associated with ADL and IADL performance in ALFs.